Process Behavior of Flower-Like Ag-Zno Micro/Nanostructures in Uv-Visible Light Photocatalytic and Antibacterial Activity - Quek, Jian Ai (2017)
Wastewater effluents which contain Fast Green (FG) dye and Escherichia coli (E.coli) exhibited human health hazards and significant researches were committed toward it. Comprehensive treatment methods were developed and amongst them, heterogeneous photocatalyst integrating silver doped zinc oxide (Ag-ZnO) as potential wastewater treatment. In this study, Ag-ZnO photocatalyst was synthesized with co-precipitation-photodeposition methods. Characterization tests such as fieldemission scanning electron microscopy (FESEM), UV-visible diffuse reflectance spectroscopy (UV-Vis DRS) and [hotoluminescence (PL) analysis were conducted. FESEM analysis identified as-produced Ag-ZnO as 3D micro/nanoflowers structures and UV-Vis DRS analysis identified the reduction in band gap of Ag-ZnO samples. Furthermore, PL analysis revealed Ag attachment onto ZnO had low emission peak. As-synthesized 5.0 wt% Ag-ZnO also exhibited superior photocatalytic degradation of FG dye compared to commercial ZnO, commercial TiO2, pure ZnO and different Ag loadings of Ag-ZnO under 240 min of UV-Vis irradiation. Moreover, 5.0 wt% Ag-ZnO settled first in the sedimentation test. Initial dye concentration and solution pH were tested for the degradation of FG dye. Under optimized condition of 2.5 ppm FG concentration and natural pH of pH 6.65, complete photocatalytic degradation and mineralization of FG dye was attained under 240 min. The investigation of active species roles had demonstrated that superoxide radicals anions (•O2‾) and photogenerated holes (hVB + ) played major roles in the photocatalytic reaction, while hydroxyl (•OH) radicals showed a lesser extent. Besides that, antibacterial response screening was also tested under 180 min with 5.0 wt% Ag-ZnO. Under UV-Vis light, 107 of E.coli colonies were disinfected. Lastly, membrane integrity assay was conducted and its result observed that 5.0 wt% Ag-ZnO produced the highest leakage of DNA absorbance within 180 min under UV-Vis light.